Effect of luteolin on apoptosis, MAPK and JNK signaling pathways in guinea pig chondrocyte with osteoarthritis - Xue, Jianli; Ye, Jintao; Xia, Zhuqing; Cheng, Bin (Cellular and Molecular Biology, 2019)
Osteoarthritis (OA) is a degenerative joint disease usually seen in the elderly, which incidence increases with age. Its pathogenesis and underlying mechanism are still unclear. The disease severely affects the physical health and life quality of patients, thereby constituting a huge economic burden to family and society. Luteolin (LUT) is a natural flavonoid with multiple pharmacological properties. Many plants containing LUT have been applied in the treatment of several inflammation-related diseases due the relatively strong anti-inflammatory effects of LUT. The present study investigated the influence of LUT on cell apoptosis and inflammatory reactions in cartilage of OA guinea pigs, and its underlying mechanism. It was found that LUT effectively inhibited proliferation of OA cartilage cells, down-regulated the expressions of JNK and p38MAPK in cartilage cells of OA, and downregulated NO, TNF-Î± and IL-6. Thus, it alleviated inflammatory reactions, protected cartilage cells, and delayed cartilage degeneration.